GAMA/H-ATLAS: common star formation rate indicators and their dependence on galaxy physical parameters. Issue 2 (20th June 2016) - Wang, L.; Norberg, P.; Gunawardhana, M. L. P.; Heinis, S.; Baldry, I. K.; Bland-Hawthorn, J.; Bourne, N.; Brough, S.; Brown, M. J. I.; Cluver, M. E.; Cooray, A.; da Cunha, E.; et al.
Abstract: We compare common star formation rate (SFR) indicators in the local Universe in the Galaxy and Mass Assembly (GAMA) equatorial fields (∼160 deg 2 ), using ultraviolet (UV) photometry from GALEX, far-infrared and sub-millimetre (sub-mm) photometry from Herschel Astrophysical Terahertz Large Area Survey, and Hα spectroscopy from the GAMA survey. With a high-quality sample of 745 galaxies (median redshift 〈 z 〉 = 0.08), we consider three SFR tracers: UV luminosity corrected for dust attenuation using the UV spectral slope β (SFRUV, corr ), Hα line luminosity corrected for dust using the Balmer decrement (BD) (SFRH α, corr ), and the combination of UV and infrared (IR) emission (SFRUV + IR ). We demonstrate that SFRUV, corr can be reconciled with the other two tracers after applying attenuation corrections by calibrating Infrared excess (IRX; i.e. the IR to UV luminosity ratio) and attenuation in the Hα (derived from BD) against β. However, β, on its own, is very unlikely to be a reliable attenuation indicator. We find that attenuation correction factors depend on parameters such as stellar mass ( M * ), z and dust temperature ( T dust ), but not on Hα equivalent width or Sérsic index. Due to the large scatter in the IRX versus β correlation, when compared to SFRUV + IR, the β-corrected SFRUV, corr exhibits systematic deviations as a function of IRX, BD and T dust .